Bridging the Gap Between Certification and Performance: The Role of Work Motivation - Fransisco Taghulihi; Joulanda A M Rawis; Harol R. Lumapow (JR Education, 2026)
This study aims to examine the influence of teacher certification and work motivation on teacher performance in vocational secondary education. Teacher performance is a crucial determinant of educational quality, particularly in vocational schools where practical competence and instructional effectiveness are essential. While teacher certification has been widely implemented as a policy to improve professionalism, its actual impact on performance remains debated. Therefore, this study integrates certification and work motivation into a single analytical model to provide a more comprehensive understanding. A quantitative approach with a causal associative design was employed. The study involved 48 certified teachers at a public vocational school in Indonesia, selected using a saturated sampling technique. Data were collected through structured questionnaires using a Likert scale and analyzed using multiple linear regression, including partial (t-test), simultaneous (F-test), and coefficient of determination (R²) analyses. The findings reveal that teacher certification has a positive and significant effect on teacher performance. Similarly, work motivation significantly influences teacher performance, although with varying directional patterns that require deeper interpretation. Simultaneously, certification and motivation significantly predict teacher performance, with a high coefficient of determination (R² = 0.754), indicating that 75.4% of performance variance is explained by the model. The study highlights that certification alone is insufficient without strong intrinsic and extrinsic motivation. Therefore, educational policymakers and school leaders should not only emphasize certification programs but also foster motivational strategies to enhance teacher effectiveness. This research contributes to the literature by providing empirical evidence from the post-pandemic educational context in vocational schools.